Changes of Sagittal and Axial Alignments of Patella after Open- and Closed-Wedge High-Tibial Osteotomy: A Systematic Review and Meta-Analysis - Lee, O-Sung; Ahn, Soyeon; Lee, Yong Seuk (The Journal of Knee Surgery, 2018)
The present systematic review and meta-analysis were aimed to verify the effect of open-wedge (OW) and closed-wedge (CW) high-tibial osteotomy (HTO) on sagittal and axial alignments of the patella. A vigorous search was performed for studies that compared the changes of sagittal and axial alignments of patella after OW and CW HTO. After evaluating publication bias and heterogeneity, we aggregated variables by using the random-effects model. The weighted mean differences in sagittal and axial alignment of patella were estimated with 95% confidence intervals. Also, we analyzed the changes in sagittal alignment of various OW HTO techniques, such as uniplanar, biplanar, and retrotubercle osteotomy. Overall, 20 studies that included 831 OW HTOs and 206 CW HTOs were included in this study. Patellar height decreased after OW HTO based on the Blackburne–Peel index (BPI, mean: −0.10), and Caton–Deschamps index (CDI, mean: −0.08). However, the patellar height after CW HTO showed no change after surgery (BPI [mean: −0.02], and CDI [mean: 0.02]). Among OW HTO techniques, the retrotubercle osteotomy showed the least change in patellar height after surgery. The lateral patellar tilt decreased by 1.74 degrees, and lateral patellar shift showed no change after OW HTO. However, there was a lack of evidence to conclude the change of axial alignment of patella after CW HTO. Our results supported that the sagittal alignment of patella lowered after OW HTO. However, CW HTO maintained the constant sagittal position of the patella. Among OW HTO techniques, the retrotubercle osteotomy had the least effect on the sagittal alignment of the patella. Regarding the axial alignment of the patella, OW HTO resulted in a little change of lateral patellar tilt; however, there was little evidence to confirm the change of the axial alignment of patella after CW HTO.
Keywords: high-tibial osteotomy; closing wedge; opening wedge; patellar height; patellar tilt; meta-analysis